The glycosylation status of MHC class I molecules impacts their interactions with TAPBPR. (November 2021) - Ilca, F. Tudor; Boyle, Louise H.
Highlights: The interaction between TAPBPR and MHC-I is stronger when MHC-I lacks a glycan. TAPBPR dissociates peptides more easily from non-glycosylated MHC-I. Glycosylation status of MHC-I influences their ability to undergo peptide exchange. MHC-I trafficking through the secretory pathway will impact TAPBPR functionality. Abstract: Glycosylation plays a crucial role in the folding, structure, quality control and trafficking of glycoproteins. Here, we explored whether the glycosylation status of MHC class I (MHC-I) molecules impacts their affinity for the peptide editor, TAPBPR. We demonstrate that the interaction between TAPBPR and MHC-I is stronger when MHC-I lacks a glycan. Subsequently, TAPBPR can dissociate peptides, even those of high affinity, more easily from non-glycosylated MHC-I compared to their glycosylated counterparts. In addition, TAPBPR is more resistant to peptide-mediated allosteric release from non-glycosylated MHC-I compared to species with a glycan attached. Consequently, we find the glycosylation status of HLA-A*68:02, -A*02:01 and –B*27:05 influences their ability to undergo TAPBPR-mediated peptide exchange. The discovery that the glycan attached to MHC-I significantly influences the affinity of their interactions with TAPBPR has important implications, on both an experimental level and in a biological context.